Creating Inclusive Knowledges 2019
DOI: 10.4324/9781315121949-8
|View full text |Cite
|
Sign up to set email alerts
|

Participation in community arts: lessons from the inner-city

Abstract: In this paper we critically reflect, through the lens of liberation psychology, on our experiences of using participative community arts in work with young people and intergenerational groups in inner-city Manchester, UK. We used mixed methods to examine the impact of and engagement with community arts in two projects. One study was quasi experimental in design and used questionnaires developed by the researchers to compare Higher Education aspirations with levels of self-esteem and self-efficacy, as a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…1-2). Clennon et al (2016) further suggest that the collective gain that may be achieved by participating in community-based arts can lead to transformative social change (also see Purcell, 2009;Swindells et al, 2013). This is in contrast to community-arts-informed research, which can be created for the sake of scholarship and research (Cahnmann-Taylor, 2007;Shannon-Baker, 2015), with a concern for advancing knowledge rather than developing visually pleasing works of art that is accessible to all (Cole and Knowles, 2008).…”
Section: Community-based Arts Researchwhat Does It Achieve?mentioning
confidence: 99%
See 1 more Smart Citation
“…1-2). Clennon et al (2016) further suggest that the collective gain that may be achieved by participating in community-based arts can lead to transformative social change (also see Purcell, 2009;Swindells et al, 2013). This is in contrast to community-arts-informed research, which can be created for the sake of scholarship and research (Cahnmann-Taylor, 2007;Shannon-Baker, 2015), with a concern for advancing knowledge rather than developing visually pleasing works of art that is accessible to all (Cole and Knowles, 2008).…”
Section: Community-based Arts Researchwhat Does It Achieve?mentioning
confidence: 99%
“…This is in marked contrast to other qualitative methods, such as focus groups and interviews, which are usually applied in participatory research with people with learning disabilities (Jurowski, 2008;Povee et al, 2013), ensuring that there are problems for people who need alternative forms of communication and accessibility. Whilst research relating to community-based arts research is developing, this research has already demonstrated that it can provide specific benefits, including towards health and social well-being (Selkrig, 2011), opportunities for artistic expression (Lawson et al, 2014), self-esteem and communication (Argyle and Bolton, 2005), and transformative change (Clennon et al, 2016). Thus, by using creative and visual methods, the men were able to challenge some of the misconceptions related to learning disabilities, such as not being able to work, the discrimination that they face regarding their experiences and knowledge, and how they relate to people.…”
Section: Using Community-based Arts To Challenge Misconceptions Aboutmentioning
confidence: 99%
“…The first kind of creative engagement uses creative acts (making, modelling through different media including film, photography and storytelling) as a way of considering community and societal issues. Research into the partnerships between the Voluntary Arts and Community Sector, public and social service providers in the UK, gives evidence for the value of creative engagement between public bodies and citizens (Kagan & Duggan, 2011;Clennon et al, 2016). Value is demonstrated through the opportunity it affords for inclusivity of voices (Sarkissian et al, 2010;Kagan & Duggan, 2011;Clennon et al, 2016), and its ability to bridge divides.…”
Section: Creative Engagement Activitiesmentioning
confidence: 99%
“…Research into the partnerships between the Voluntary Arts and Community Sector, public and social service providers in the UK, gives evidence for the value of creative engagement between public bodies and citizens (Kagan & Duggan, 2011;Clennon et al, 2016). Value is demonstrated through the opportunity it affords for inclusivity of voices (Sarkissian et al, 2010;Kagan & Duggan, 2011;Clennon et al, 2016), and its ability to bridge divides. It converts historic norms of top-down engagement into the co-construction of new cultural practices and collaborative governance, with improved chances of long term success (Kagan & Duggan, 2011;Clennon et al, 2016).…”
Section: Creative Engagement Activitiesmentioning
confidence: 99%
See 1 more Smart Citation